Peculiar Features of Non-Verbal Means of Communication among Children with Normal Eyesight and Visually Challenged Children of High Preschool Age - Оkonechnikova, L (KnE Life Sciences, 2018)
It is known, that visually challenged child acquire non-verbal means of communication less spontaneously. It is more common for them to use single and definite gestures and frequently provide them with some verbal explanations, incorrect perception of gestures and miming, poorness or lack of movements. Based on A.R.Luria’s idea of the role of the environment in a child’s personality formation, and compensatory developing mechanisms and also on some ideas of modern researchers that nonverbal means of communication are connected with social conditions and usually are formed during the life with the exception of means of affective expressiveness (G.V. Grigirieva, L.I.Plaksina, L.I.Solntseva), we have made a comparative study of using nonverbal means of communication among children with normal eyesight and visually challenged children. As research approaches we modify and use such techniques as “The ABC of Mood” by N.L.Belopolskaya, “Silence game” by G.V.Grigorieva, “Understanding of gestures” by N.V.Pilipko and “Understanding of Miming” by Sabin and Hardick modified by G.V. Grigorieva. We have examined 36 children of high preschool age, 18 of them were with normal eyesight and 18 were visually challenged, and all of them were taught how to acquire non-verbal means of communication. We have found out that children from both groups could not differentiate similar facial expressions and gestures, miming usually was described through actions, not through feelings or emotions. The results showed us the absence of defining facial expressions, gestures and miming on the levelы of cognition and behavior between these two groups of children. On the level of emotions, we had had the following differences: the children with normal eyesight rarely explain gestures through actions then visually challenged children and also they rarely connect the emotional state with the situation, but more often they distinguish miming through explaining some physical characteristics, that may depend on their visual problem. So we can conclude that if we organize the process of education in the right way (the role of the environment) visually challenged pre-school aged children can have the partial ability to compensate their acquirement of non-verbal means of communication. Keywords: non-verbal means of communication, expressions, gestures, miming, pre-school aged children, visually challenged.